Phthalocyanine‐Assembled Nanodots as Photosensitizers for Highly Efficient Type I Photoreactions in Photodynamic Therapy - Li, Xingshu; Lee, Dayoung; Huang, Jian‐Dong; Yoon, Juyoung (Angewandte Chemie International Edition, 2018)
Owing to their unique, nanoscale related optical properties, nanostructures assembled from molecular photosensitizers (PSs) have interesting applications in phototheranostics. However, most nanostructured PS assemblies are super‐quenched, thus, preventing their use in photodynamic therapy (PDT). Although some of these materials undergo stimuli‐responsive disassembly, which leads to partial recovery of PDT activity, their therapeutic potentials are unsatisfactory owing to a limited ability to promote generation reactive oxygen species (ROS), especially via type I photoreactions (i.e., not by 1O2 generation). Herein we demonstrate that a new, nanostructured phthalocyanine assembly, NanoPcA, has the ability to promote highly efficient ROS generation via the type I mechanism. The results of antibacterial studies demonstrate that NanoPcA has potential PDT applications. Photodynamic nanodots self‐assembled from phthalocyanine molecules (NanoPcA) display highly efficient reactive oxygen species generation via a type I mechanism. Antibacterial studies demonstrate that NanoPcA has potential photodynamic therapy applications.